Pouchitis-Associated Iritis (Uveitis) Following Total Proctocolectomy and Ileal Pouch-to-Anal Anastomosis in Ulcerative Colitis - Hugh James Freeman (Canadian Journal of Gastroenterology)
A 26-year-old woman with ulcerative colitis treated with a proctocolectomy and ileal pouch-to-anal anastomosis developed an erosive and ulcerative pouchitis. Although no ophthalmological manifestations were present before the staged surgical procedures, iritis developed after appearance of the pouchitis. Both conditions subsequently resolved with oral corticosteroids and metronidazole.